An Application of Systemic Functional Grammar on Rilke's poem "Walk". - Lashari, Mubarak Ali; Bughio, Faraz Ali (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
The intention, this study was launched with, was to explore the applicability of the Systemic Functional Grammar, the linguistic development promoted by famous linguist M.A. K. Halliday. The theory establishes the view of functionality of linguistic phenomena in the pieces of literature. The study in hand is aimed to find the functional elements in Rainer Maria Rilke's poem "Walk". The poem was analyzed into three major functional methods of the theory including Ideational, Interpersonal and Textual analysis. In the first category, the transitivity patterns and the clauses having active and passive voices were analysed. In the second, the interpersonal elements; having the persons involving in the process and showing relationship with each other were seen. And finally, the textual meaning and the sense emerging from all the above findings were discussed. It further sought the theme of the poem and the basic functional idea of the poetic expression. And in the final stage the emanating message of the poem was discussed in the conclusion.